Estimating gross value added volumes and prices by institutional sector - Elisabeth Wieland; Ilja Kristian Kavonius (European Central Bank (ECB), 2016)
Integrated quarterly sector accounts (QSA) provide an analytical tool to understand the generation, allocation and use of income for all institutional sectors in the economy. They also provide a tool to analyse production from a sectoral point of view instead of an industry point of view. However, since QSA are published in current prices only, sectoral volume and price measures are lacking as an important toolkit for economic analysis and forecasting, notably in the case of gross value added. This paper introduces a methodology to estimate sectoral price and volume measures for euro area value added at a quarterly frequency and provides a comparison of alternative estimation methods. It presents a benchmark method which yields robust estimates of sectoral volumes and prices in the euro area.
Keywords: C33; C82; E01; E30; 330; institutional sector; national accounts; price; production account; value added; volume